INFLUENCE OF PERSONAL PSYCHOLOGY, CULTURE AND DEMOGRAPHY ON PAYMENT DECISIONS ON BANK SYARIAH INDONESIA - Sriwahyuni, Sriwahyuni; Nasution, Muhammad Lathief Ilhamy; Anggraini, Tuti (Sharia Banking Study Program, Faculty of Islamic Economics, Djuanda University, Bogor, 2025)
The purpose of this study is to examine the factors that influence consumers decisions to select murabahah contracts from Islamic banks. This kind of study is quantitative study involving all Bank Syariah Indonesia KC. Kutacane, Southeast Aceh users. The sampling number was 52 respondents who used purposive sampling by filling out the questionnaire provided. The methods used to the hypothesis is tested using a variety of techniques, including traditional hypothesis testing, hypothesis testing, testing for multiple regressions, and determination coefficient testing. The analysis this study's tool makes use of SPSS versions 22 and 24. The research results indicate that the research results of the internal factor study consisting of psychology and personality partially influence customer decisions because the value of the t count (6.931) > t table (2.00) and the significant level is 0.000 < 0.05. The research results of the external factor study consisting of culture and demographics partially influence consumer decisions because the value of the t count (4.026) > t table (2.00) and the significant level is 0.000. The study's findings show that internal factors made up of psychology and personality and external factors consisting of culture and demographics simultaneously influence customer decisions because the calculated f value (69.626) > f table (3.18) and the significant level is 0.000 < 0.05.